ACVRL1 gene variant in a patient with vein of Galen aneurysmal malformation - Chida, Ayako; Shintani, Masaki; Wakamatsu, Hajime; Tsutsumi, Yoshiyuki; Iizuka, Yuo; Kawaguchi, Nanako; Furutani, Yoshiyuki; Inai, Kei; Nonoyama, Shigeaki; Nakanishi, Toshio (Journal of Pediatric Genetics, 2013)
Although mutations in the RASA1 gene in vein of Galen aneurysmal malformation (VGAM) and an endoglin gene mutation in a VGAM patient with a family history of hereditary hemorrhagic telangiectasia (HHT) have been identified, most VGAM cases have no mutation in these genes. We sought to detect mutations in other genes related to HHT. We screened for mutations in RASA1 and three genes (endoglin, activin receptor-like kinase 1 (ACVRL1), encoding ALK1, and SMAD4) related to HHT in four VGAM patients. One variant (c.652 C>T p.R218W) in ACVRL1 was identified. Immunoblotting revealed that the ALK1-R218W protein could not promote SMAD1/5/8 phosphorylation by BMP9 stimulation. On the other hand, wild-type ALK1 could enhance the phosphorylation as expected. Furthermore, the transcriptional activation of ALK1-R218W was less efficient than that of wild-type ALK1. We identified 1 variant in ACVRL1 in a VGAM patient. These findings suggest that the ACVRL1 variant-R218W may be associated with the pathogenesis of VGAM.
Keywords: ACVRL1; gene variant; vein of Galen aneurysmal malformation